Exotic parodies : subjectivity in Adorno, Said, and Spivak - Varadharajan, Asha (University of Minnesota Press, 1995)
This groundbreaking text begins with the premise that postmodernism, poststructuralism, postcolonialism, and Marxism continue to present certain problems with the self/other distinction. It goes on to offer the first extended critique of the work of Gayatri Spivak; challenge the critical reception of Adorno in the American academy; examine Said's connection to Adorno; and make the first in-depth use of Adorno's Negative Dialectics in the context of postcolonial theory.